The PENGEMBANGAN MEDIA PEMBELAJARAN PETI ILMU PERSUASI PADA MATERI TEKS PERSUASI SISWA KELAS VIII SEKOLAH MENENGAH PERTAMA NEGERI 7 TANJUNGPINANG TAHUN AJARAN 2022/2023 - wanda, wanda monika putri; Legi Elfitra; Siti Habiba (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research has the aim of developing a media for teaching the science of persuasion in persuasive text material for class VIII students of SMP Negeri 7 Tanjungpinang for the academic year 2022/2023. This study uses the 4D development model up to the development stage. The product developed in this study is a visual-based learning media with the basic ingredients of plywood and brown in color. This learning media has been assessed based on the assessment of two experts, namely media experts and material experts. The number of students in this media trial was 6 students for small groups and 36 students for large groups. Data collection techniques in this study, namely interviews, media validation questionnaires by media experts and material experts, as well as media practicality questionnaires by students. Data analysis techniques in this study were carried out using two techniques, namely descriptive qualitative and descriptive quantitative. The results of this study obtained an average of 93% with the criteria of "very valid" for the media, an average of 95% with the criteria of "very valid" for the material. In addition, this research was tested on students who obtained an average of 84% with the criteria of "very practical" by small groups and an average of 90% with the criteria of "very practical" by small groups.